TRANSFORMASI EKONOMI PESISIR BERKELANJUTAN MELALUI INOVASI HIJAU DAN GREEN HUMAN RESOURCE MANAGEMENT: KAJIAN SISTEMATIS PADA PROGRAM KAMPUNG NELAYAN MERAH PUTIH - Sri Widanarni; Roby Sambung; Jonathan Giovanni; Nurlia Eka Damayanti; Kembara Sopather; Normand Armando Lampe; Aprilita Aprilita (STKIP Persada Khatulistiwa Sintang, 2026)
This study systematically examines the interrelationship between green human resource management (GHRM), green innovation, and the blue economy in promoting sustainable coastal development in Indonesia. Using a Systematic Literature Review (SLR) approach, this research analyzes 65 peer-reviewed academic articles published between 2021 and 2025. The review identifies four major thematic clusters: (1) the implementation of GHRM practices, (2) the linkage between GHRM and green innovation, (3) the role of green innovation in socio-coastal contexts, and (4) the integration of GHRM and green innovation within the blue economy framework. The findings indicate that GHRM plays a critical role in shaping environmental competencies, pro-environmental behavior, and organizational learning, which collectively stimulate green innovation. Furthermore, the integration of GHRM and green innovation strengthens the socio-economic resilience of coastal communities while supporting sustainable marine resource management. However, the literature also reveals limited empirical application of GHRM in community-based coastal development, particularly within developing regions. This study contributes by offering a human-centered and knowledge-based conceptual framework for sustainable coastal development, providing strategic insights for policymakers, local governments, and development practitioners to enhance the implementation of the blue economy through strengthened human resource capacity and environmental innovation.